Revisiting The Penetration Of Islam In The Philippines And Its Implication For The Development Of Muslim Institutions - Alizaman D. Gamon; Mariam Saidona Tagoranao (International Islamic University Malaysia (IIUM), 2024)
Indexed by ERA/MYCITE